Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/ajg.2010.294
|View full text |Cite|
|
Sign up to set email alerts
|

Peginterferon Plus Ribavirin and Sustained Virological Response in HCV-Related Cirrhosis: Outcomes and Factors Predicting Response

Abstract: SVR can be achieved in approximately one-third of patients with HCV-related cirrhosis. SVR independently reduces the likelihood of clinical decompensation and improves survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 20 publications
1
33
0
2
Order By: Relevance
“…A prospective 12-year follow-up study of 218 compensated HCV-induced cirrhotic patients in Italy indicated that SVR achievement after interferon therapy prevented the development of esophageal varices [121]. A retrospective study that examined 568 HCV patients with liver cirrhosis undergoing pegylated interferon-α and ribavirin treatment indicated that SVR was achieved in approximately one-third of patients with HCV-related cirrhosis, independently reducing the likelihood of clinical decompensation and improving survival [122]. SVR in HCV patients markedly reduces clinical complications and improves portal hypertension [123].…”
Section: Treatment For Viral Hepatitis-related Liver Fibrosis and mentioning
confidence: 99%
“…A prospective 12-year follow-up study of 218 compensated HCV-induced cirrhotic patients in Italy indicated that SVR achievement after interferon therapy prevented the development of esophageal varices [121]. A retrospective study that examined 568 HCV patients with liver cirrhosis undergoing pegylated interferon-α and ribavirin treatment indicated that SVR was achieved in approximately one-third of patients with HCV-related cirrhosis, independently reducing the likelihood of clinical decompensation and improving survival [122]. SVR in HCV patients markedly reduces clinical complications and improves portal hypertension [123].…”
Section: Treatment For Viral Hepatitis-related Liver Fibrosis and mentioning
confidence: 99%
“…Como prueba de ello, se ha comunicado una probabilidad significativamente menor del riesgo de descompensación y del riesgo de muerte en pacientes cirróticos por alcohol, por virus B y por virus C de la hepatitis, las tres causas más relevantes de enfermedad hepática de manera global [30][31][32][33] . Especialmente relevante resulta en el escenario actual la posibilidad de curar la hepatitis crónica por virus C en la inmensa mayoría de los pacientes, incluyendo aquellos con cirrosis evolucionada y con un perfil virológico de mala respuesta a tratamientos previos.…”
Section: Complicaciones Pronósticounclassified
“…SVR esetén 49%-ban észlelték a fi brosis regresszióját, de 12%-ban új cirrhosis jelentkezését is regisztrálták, 10 év után mindössze 5%-ban volt igazolható a cirrhosis regressziója, és 5% esélye volt a HCC kialakulásának SVR-betegekben is [27]. Fernández-Rodríguez és mtsai szerint P/R kezelt HCV-cirrhosisban 5 éves mortalitás SVR esetén 2%, nem SVR-betegekben 14% volt [28]. Hézode és mtsai csak az SVR-betegekben észlelték a fi brosis regresszióját.…”
Section: A Terápiás Válasz Monitorozásaunclassified